A Bibliography of Philippine language dictionaries and vocabularies - Hendrickson, Gail R.; Newell, Leonard E. (Manila Linguistic Society of the Philippines, 1991)
It includes a complete listing of dictionaries and vocabularies (published and unpublished) of the Philippine languages. It is listed in a bilingual vocabulary arranged chronologically.
It includes manuscripts and published works of vocabularies and dictionaries of the Philippine languages restricted to the Malayo-Polynesian languages within the political boundaries of the Republic of the Philippines.
Keywords: Philippine languages -- Dictionaries; Philippine languages -- Bibliography; Philippine languages -- Glossaries, vocabularies, etc